The ‘professional digital competence’: exploring the perspective of primary music teachers in Spain. - Mateos-Moreno, Daniel; Bravo Fuentes, Paloma (SAGE, 2023)
The terms ‘Digital competence’ or ‘Professional digital competence’ are frequently used, yet their understanding remains varied and elusive. Moreover, existing research in education heavily focuses on the study of digital competence among students, with comparatively limited attention given to teachers. In this study, we aim to investigate primary music teachers’ perspectives on ‘professional digital competence’ in Spain. This entails understanding their conceptualizations on (1) the term itself, (2) the cultivation of related skills and (3) its practical application with students. Additionally, we seek to compare primary music teachers’ viewpoints with those of teachers from other subjects. Through a qualitative multi-case study involving purposeful sampling of 20 participants, the results suggest that our music teachers, regardless of their self-stated technological skills, possess a limited understanding of the ‘professional digital competence’ and express negative or pessimistic beliefs towards its development and implementation. Furthermore, they feel compelled to use educational technology despite their reservations. Our findings similarly indicate that their beliefs are not meaningfully different from those of non-music teachers in the same context. In discussing the implications, we suggest that these beliefs may lead to stress and anxiety among participants, necessitating support from educational administrators. Additionally, we propose that future research should further investigate both why and how our participants feel/are pressured to use technology, and the particular disadvantages of technology in music education identified in our analysis of their beliefs.
Keywords: Investigación activa en educación; Música - Estudio y enseñanza; Competence; Digital; Education; Music; Teachers